Political Participation of Armenian minority in Georgia - Stanislav Mezhdoyan (European Regional Science Association (ERSA), 2015)
The purpose of the paper is to analyze political participation of Armenian minority in Georgia, find out the obstacles that government of Georgia and minorities face. To analyze and compare the international legal base in the field of political integration of minorities as a key to solution for issue existed in Georgia.
Keywords: 330